The Electoral Consequences of Economic Inequality in Finland: The Case of the Finns Party - Bahamonde Hector; Koivula Aki (Turun yliopisto, 2026)
It is not new to social scientists that economic downturns affect voting decisions. Thus, since politics is the realm where decisions are made about “who gets what, when, and how,” the unemployment rate, economic growth and income distribution will inevitably influence people’s minds when it comes to voting.